Odpowiedzi

2010-03-03T18:08:17+01:00
B*(c-d)
x*(y-3)
y*(9x-1)
b*(a+3b)
1 1 1
2010-03-03T18:10:42+01:00
a(2ab + b) - b(a - 2ab + a²)=2a²b+ab-ab+2ab²-a²b=2ab²+a²b=2(0,01*(-10))-0,1= -0,2-0,1=-0,3

bc-bd=b(c-d)
xy-3x=x(y-3)
9xy-y=y(9x-1)
ab + 3b²=b(a+3b)
1 1 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-03T18:15:46+01:00
B) a(2ab + b) - b(a - 2ab + a²)=2a²b+ab-ab+2ab²-a²b=a²b+2ab²= (-0,1)²*(-10)+2*0,1*(-10)²= -0,1+20=19,9

a) bc-bd=b(c-d)
b) xy-3x=x(y-3)
c) 9xy-y=y(9x-1)
d) ab + 3b² =b(a+3b)
2 3 2